First report of Wohlfahrtiimonas chitiniclastica from soft tissue and bone infection at an unusually high northern latitude - Kõljalg, Siiri; Telling, Kaidi; Huik, Kristi; Murruste, Marko; Saarevet, Virve; Pauskar, Merit; Lutsar, Irja (Folia microbiologica, 2015)
Wohlfahrtiimonas chitiniclastica is a rare human pathogen mostly associated with parasitic flies. This is the report on W. chitiniclastica infection in the soft tissue and bone at a 58°N latitude in the northern temperate climate zone. The importance of correct identification of clinically relevant bacteria is highlighted.
Keywords: Molecular Sequence Data; Sequence Analysis, DNA; Soft Tissue Infections; infekce měkkých tkání; RNA, Ribosomal, 16S; Estonsko; DNA, Bacterial; Middle Aged; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; mužské pohlaví; osteomyelitida; DNA, Ribosomal; gramnegativní bakteriální infekce; DNA bakterií; Xanthomonadaceae; RNA ribozomální 16S; Humans; Osteomyelitis; ribozomální DNA; Gram-Negative Bacterial Infections; Estonia; lidé středního věku; sekvenční analýza DNA; spektrometrie hmotnostní - ionizace laserem za účasti matrice; molekulární sekvence - údaje; lidé; Male